Western scholars on samurai: Stages in studying the Japanese military estate of the 18th – early 20th century - E.A. Pavlovskaya (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to the study of the military estate of Japan by British and American scholars since the discovery of the country in 1853 until the World War I. Their transactions are valuable because the authors wrote about samurai during the period when they existed. In Russia these works have not attracted attention of scholars. The paper is aimed at analyzing the first scientific and journalistic works from the point of view of their evaluation of samurai, as well as the origin of scientific study of Japanese history. In this period three stages were identified. 1) Protoscientific (until 1869). Lack of terminology and single perception of the Japan history, inaccessibility of sources, and, as a consequence, inaccuracy of information. The focus of attention of Europeans was the shogunate and the daimyo. 2) Early scientific (1869–1894). The beginning of cooperation between Western and Japanese scientists, active work of the founders of western Japanese studies – E. Satow, W. Aston, B.H. Chamberlain, W.E. Griffis, et al. The beginning of the “Asiatic Society of Japan”. The rise of interest in samurai as a marginal stratum of society. 3) Popular-science (1894–1914). Japan military victories led to an increase in the number of popular literature about the Sino-Japanese and Russo-Japanese war and, as a result, the interest in samurai and their ethics has increased.